Valina em dietas para tilápia do Nilo (Oreochromis niloticus) - RODRIGUES, Rômulo Batista (2016)
The valine is part of the branched chain amino group together with leucine and isoleucine, and has an important structural role and anabolic. Two experiments were conducted in order to determine the requirement of valine for fingerlings and juveniles of tilapia, by assessing the growth performance, and analysis of chemical composition of housing, hematological and biochemical blood, and white muscle morphometric. In the first experiment were used 270 tilapia fingerlings whit initial average weight of 1.57 ± 0.05 g total initial length of 4.16 ± 0.46 cm, distributed in completely randomized design with six treatments and three replications, using 18 boxes with 250 liter of capacity during the experimental period of 79 days. In the second experiment were used 216 tilapia juveniles with initial average weight of 21.40 ± 0.42g and initial total length of 10.07 ± 1.00 cm, distributed in 18 boxes whit 500 liters of capacity during the experimental period of 77 days. The treatments consisted of diets with increasing concentrations of valine, being for fingerlings (0.82, 0.86, 0.98, 1.04, 1.10 and 1.26% valine) and juvenile (0.54, 0.63, 0.72, 0.81, 0.90 and 0.99% valine). Feed has been held four times a day to apparent satiation. Evaluated the growth performance (weight gain, feed conversion, daily weight gain, protein efficiency ratio, condition factor, survival, protein retention efficiency, visceral fat, liver somatic index, specific growth rate and uniformity of the lot) for fingerlings and juveniles; fish proximate composition (moisture, crude protein, lipids and ash) for fingerlings and juveniles; hematological and biochemical indices of the blood (hemoglobin, erythrocytes count, hematocrit percent, total leukocytes, total thrombocytes, plasma protein, glucose, triglyceride and cholesterol) for juvenile and distribution of muscle fibers to fingerlings and juveniles. There was no statistical difference (P>0.05) for the performance variables, chemical composition and histology between the different treatments evaluated to fingerlings. For juvenile tilapia, on the performance were observed significant differences (P<0.05) between treatments for weight gain, daily weight gain and feed conversion. For hematological and biochemical parameters of blood, there were significant differences (P<0.05) between treatments for hemoglobin, total triglycerides and total cholesterol. Significant differences in the chemical composition of fish and frequency of muscle fibers were observed. It is concluded that the nutritional requirements are met with valine 0.82% valine in the diet (2.65% valine crude protein) for minnows and 0.81% of valine in the diet (2.90% valine crude protein) for juvenile Nile tilapia.